Penanggulangan Pemutusan Hubungan Kerja Buruh Sebagai Akibat Permasalahan Penagihan Penyelenggara Teknologi Finansial - Putri, Clarisa Permata Hariono; Kurniawan, Cindy Cornelia; Thio, Stevie (Kertha Patrika; Vol 46 No 1 (2024)DO - 10.24843/KP.2024.v46.i01.p02, 2024)
Termination of labor relations as a result of billing problems from financial technology providers has occurred in Indonesia. The aim of the research is to determine the legal position of financial technology billing issues as a cause of termination of labor relations and specifically to analyze the forms of countermeasures that can be taken against these legal facts from a legal perspective, especially labor law, where employment plays an important role as a determining factor in state development. This research is normative legal research with two approaches, namely the statutory and conceptual approaches. The results of the research conclude that financial technology billing problems can be one of the reasons for termination of employment as long as they fulfill the three requirements in Article 154A paragraph (1) letter k of Employment Law jo. Job Creation Law and there are several forms of countermeasures need to be carried out both preventively as the main effort by the mandate of Article 151 of Employment Law jo. Job Creation Law and in a repressive manner. This effort must be carried out by all three parties in industrial relations, namely the government, workers, and employers by the provisions of Article 1 number 16 jo. Article 102 of Employment Law jo. Job Creation Law.